Linguistische Beitraege zur Slavistik aus Deutschland, Oesterreich und der Schweiz III. JungslavistInnen-Treffen Hamburg 1994. Unter Mitwirkung von E. Rauchenecker u. D. Marszk - Dippong, Horst (Specimina philologiae Slavicae, 1995)
This volume documents the Third Meeting of the Boys' Slaves, which took place from 30 September to 2 October 1994 in Hamburg. The meetings are understood to be workshops with a certain workshop character, the participants consciously recruit from the circle of junior slavists who are not yet habilitated and / or in a position of life. In keeping with the workshop character, contributions were also presented at the meeting which, as components of more comprehensive work or as interim results of larger projects, were not intended for publication in the given context. These are Sylke Eichler (Leipzig), Dorothee Fehrmann (Leipzig), Robert Hammel (Göttingen), Uwe Junghanns (Berlin) and Jana Schulze (Leipzig / Bautzen).